2014
DOI: 10.1073/pnas.1317860111
|View full text |Cite
|
Sign up to set email alerts
|

Processing multiple visual objects is limited by overlap in neural channels

Abstract: High-level visual categories (e.g., faces, bodies, scenes, and objects) have separable neural representations across the visual cortex. Here, we show that this division of neural resources affects the ability to simultaneously process multiple items. In a behavioral task, we found that performance was superior when items were drawn from different categories (e.g., two faces/two scenes) compared to when items were drawn from one category (e.g., four faces). The magnitude of this mixed-category benefit depended … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

14
141
1
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 101 publications
(157 citation statements)
references
References 47 publications
14
141
1
1
Order By: Relevance
“…This finding is consistent with those from verbal working memory, which show better memory for phonologically dissimilar than similar words (Baddeley, 1966). They support theories such as the multiple-resource theory (Olson & Jiang, 2002;Wheeler & Treisman, 2002) or its neural instantiation -the cortical resource theory (Cohen et al, 2014). Dissimilar stimuli yield better memory because peaks of neural activation for these stimuli are widely separated, minimizing interference.…”
supporting
confidence: 85%
See 1 more Smart Citation
“…This finding is consistent with those from verbal working memory, which show better memory for phonologically dissimilar than similar words (Baddeley, 1966). They support theories such as the multiple-resource theory (Olson & Jiang, 2002;Wheeler & Treisman, 2002) or its neural instantiation -the cortical resource theory (Cohen et al, 2014). Dissimilar stimuli yield better memory because peaks of neural activation for these stimuli are widely separated, minimizing interference.…”
supporting
confidence: 85%
“…One pattern of data suggests that similarity is detrimental. For example, memory for an array of faces and scenes is better than memory for just faces or scenes (Cohen, Konkle, Rhee, Nakayama, & Alvarez, 2014). This finding is consistent with those from verbal working memory, which show better memory for phonologically dissimilar than similar words (Baddeley, 1966).…”
supporting
confidence: 83%
“…Alternatively, one may argue that all dimensions of the stimuli are processed, so that the digits embedded in leet words are processed not only as letters but also as numerical quantities. Indeed, a positive answer to this question would strongly suggest that, upon presentation of visual stimuli, there is activation from multiple codes (quantities, lexical representations) in the cognitive system (see Cohen et al, 2014). To tease apart these two explanations, we employed a physical-size judgment tasks with leet words.…”
mentioning
confidence: 99%
“…Importantly, there are proposals that relate the ability of our cognitive system to process multiple representations of a given stimulus at once with the neural overlap between the categories of the items presented. In an experiment using functional neuroimaging, Cohen et al (2014) found that the ability to process stimuli from different categories (e.g., faces vs scenes) in a single presentation was predicted by the amount of separation between neural response patterns, particularly within occipitotemporal cortex. The idea was that neural overlap would imply sharing resources whereas non-overlapping neural representations would imply separate representational resources (Cohen et al, 2014).…”
mentioning
confidence: 99%
See 1 more Smart Citation